Advances in chemistry and bioactivity of parthenolide - Freund, Robert R A; Gobrecht, Philipp; Fischer, Dietmar; Arndt, Hans-Dieter (Natural product reports, 2020)
Review covering up to 07/2019(-)-Parthenolide is a germacrane sesquiterpene lactone, available in ample amounts from the traditional medical plant feverfew (Tanacetum parthenium). Acting as a covalently reactive compound, it displays anti-inflammatory, redox-modulating, and epigenetic activities, as well as selective cytotoxicity towards cancer stem and progenitor cells. Furthermore, parthenolide was found to modulate microtubule dynamics by interfering with the detyrosination of α-tubulin, a specific posttranslational modification of the cytoskeleton. This review interfaces recently achieved parthenolide syntheses with strategies for bioactivity-based derivatization. Furthermore, chemical probe development from parthenolide is discussed, leading to a qualified summary of reported biological activities and implicated or identified targets. Special emphasis is given to parthenolide-induced microtubule modulation and the recently characterized tubulin carboxypeptidase enzymes involved in nerve (re)growth, cardiac muscle cell function, and metastasis development.